Three Macroeconomic Trends Around the Onset of Armed Conflict in Developing Economies - Lederman, Daniel; Rojas, Claudio J. (World Bank, Washington, DC, 2018)
This paper studies the evolution of three macroeconomic variables (namely current fiscal expenditures, public debt, and consumer-price inflation) around the time of the onset of armed conflicts during 1950-2016. The authors compare the performance of these variables in conflict-afflicted economies with economies that did not experience social conflict. The analyses cover episodes of conflict from around the world and study the evolution of these variables during the five years prior to and five years after the onset of conflicts. Further, four alternative definitions of social conflict are used to ascertain the robustness of the econometric results. The evidence suggests that current fiscal expenditures and public debt (both as a share of gross domestic product) in conflict-afflicted economies tend to be higher than in non-conflict economies prior to the onset of conflict, begin to rise further prior to the date of the onset of conflict, and stay relatively high after the onset of conflict. In contrast, there is little evidence that inflation is higher in conflict-afflicted economies, prior to or after the onset of conflict. These differential trends between conflict-afflicted and non-conflict economies shed new light on the existing literature on macroeconomic populism, and on key macroeconomic aspects of the economics of post-conflict reconstruction.